Afroanomalia pseudoclistopyga, a new genus and species of pimpline parasitoid wasp (Hymenoptera: Ichneumonidae: Pimplinae) from the Afrotropical region - Varga, Oleksandr (Zootaxa, 2018)
Afroanomalia pseudoclistopyga gen. & sp. n. from Burundi is described and illustrated. The new genus is distinguished from all other Pimplinae by the combination of the following characters: occipital carina dorsally distinct and straight; pronotum strongly swollen laterally, wider than mesoscutum in dorsal view; propodeum elongate, submetapleural carina absent, at least distally; fore wing with vein 3rm absent, hind wing with distance between distal abscissa of Cu1 and M longer than vein cu-a, female hypopygium large and projecting; ovipositor long and straight, lower valve with strongly backwards projecting apical teeth.